KAJIAN FUNGSI “EASY SIDE TABLE” PADA RUANG BELAJAR DENGAN LAHAN TERBATAS - Irma Damayantie; Oskar Judianto (Universitas Bina Sarana Informatika, 2020)
Our daily activities are always filled with information. One of the sources of information is we get through learning. Furniture to support learning activities at home, including tables, chairs, bookshelves, etc. We need a place as comfortable as possible to study, especially at home. Currently, one solution for those who still want to live in big cities is to buy a small residential unit that must be sufficient to live with their family. In this article, we will discuss a study table placed in a narrow space. The multipurpose table design will be studied as a solution that serves to support learning activities in limited spaces. This is important because no matter how small we live, the factor of comfort when studying should not be abandoned. The author will use a phenomenological approach that involves all the five senses in observing the study table. The author will provide a description of the experiences experienced while researching the